Impact of Climate Change Adaptation Strategies on Winter Wheat and Cropping System Performance across Precipitation Gradients in the Inland Pacific Northwest, USA - Maaz, Tai M.; Schillinger, William F.; Machado, Stephen; Brooks, Erin; Johnson-Maynard, Jodi L.; Young, Lauren E.; Young, Frank L.; Leslie, Ian; Glover, Ayana; Madsen, Isaac J.; Esser, Aaron; Collins, Harold P.; et al. (Frontiers in Environmental Science, 2017)
Ecological instability and low resource use efficiencies are concerns for the long-term productivity of conventional cereal monoculture systems, particularly those threatened by projected climate change. Crop intensification, diversification, reduced tillage, and variable N management are among strategies proposed to mitigate and adapt to climate shifts in the inland Pacific Northwest (iPNW). Our objectives were to assess these strategies across iPNW agroecological zones and time for their impacts on 1) winter wheat (Triticum aestivum L.) productivity, 2) crop sequence productivity and 3) N fertilizer use efficiency. Region-wide analysis indicated that WW yields increased with increasing annual precipitation, prior to maximizing at 520 mm yr-1 and subsequently declining when annual precipitation was not adjusted for available soil water holding capacity. While fallow periods were effective at mitigating low nitrogen (N) fertilization efficiencies under low precipitation, efficiencies declined as annual precipitation exceeded 500 mm yr-1. Variability in the response of WW yields to annual precipitation and N fertilization among locations and within sites supports precision N management implementation across the region. In years receiving less than 350 mm precipitation yr-1, WW yields declined when preceded by crops rather than summer fallow. Nevertheless, WW yields were greater when preceded by pulses and oilseeds rather than wheat across a range of yield potentials, and when under conservation tillage practices at low yield potentials. Despite the yield penalty associated with eliminating fallow prior to WW, cropping system level productivity was not affected by intensification, diversification, or conservation tillage. However, increased fertilizer N inputs, lower fertilizer N use efficiencies, and more yield variance may offset and limit the economic feasibility of intensified and diversified cropping systems.